The Chevron Effect Further Demystified through the Lower Bound Theorem - McManus, Patrick; Puckett, Jay (Engineering Journal, 2025)
The transfer of brace forces at braced frame connections in V, inverted-V, and X brace configurations is discussed. Force transfer under these configurations considers both wide-flange (WF) and rectangular hollow structural sections (HSS) for the horizontal beam or strut. The analogous condition of truss web-to-chord connections using gusset plates is discussed. Analogies are expanded to address the condition of beam-to-column brace connections using a common gusset plate to receive the horizontal beam/strut and braces above and below the beam/strut. The potential to redistribute forces using the assumptions of the lower bound theorem is investigated. Additionally, the transposition of shear forces to axial forces in connections at X-brace configurations is illustrated. In conclusion, several methods can address the transfer of brace forces in gusset plate connections. Shear forces in the beam/strut, truss chord, or column members for the various conditions can be reduced by redistributing forces to properly proportioned gusset plates using the assumptions of the lower bound theorem. A reduction in shear forces in the primary members can effectively avoid localized member reinforcement, such as doubler plates or upsizing of members.